Children of war : diaries 1941-1945 - Zjatʹkov, Nikolaj 1950- HerausgeberIn; Bromfield, Andrew ÜbersetzerIn; France, Rose ÜbersetzerIn; Hippisley, Anthony R. ÜbersetzerIn (Argumenty i fakty, AIF Kind Heart Charitable Foundation, 2016)
"... gathered together all the surviving diaries written by Russian children during the Second World War that it has been possible to find, and now, for the first time in seventy years, the [sic] these diaries have been brought together in a single volume ... more than half of the thirty-five diaries included in this collection are published here for the first time"--Back cover